Historical blocking: CN 2019-02-14 (China) - Voidly (2019)
CRITICAL severity censorship detected in China. Confidence: 80%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2019-0005
Keywords: censorship; CN; censorship; critical